Wet-nurses in the ABC newspaper (1903-1920) - Antonio Martinez-Sabater; Jesús Juárez-Colom; José Siles-González; María del Carmen Solano-Ruiz (Universidad de Alicante, 2017)
In the process of infant feeding throughout history, one of the options has been the support by wet nurses, in both household and institutional level. This social figure has been reflected in press and can be studied in terms of its representation. We set as our goal to acquire a social vision through the analysis of a corpus of documents from the newspaper ABC of Madrid between 1903 and 1920. The method used has been the search of the term wet nurse through the review and content analysis of the ABC, in news, advertisements and other references in the period indicated. 999 documents have been recovered and analyzed, 41% corresponding to wet nurses offers and demands, 24% to advertisements and products related to food and/or food supplements. The remaining records correspond to economic measures, legislative rules, references to wet nurses of royalty or social references. Qualitative content analysis clarifies the social vision of wet nurses in society at that time. The study concludes that wet nurses are presented as a normalized social figure and as such is reflected in the press, which will also reflect the negative view of these women influenced by the hygienist current.